Energy Taxis toward Host-Derived Nitrate Supports a Salmonella Pathogenicity Island 1-Independent Mechanism of Invasion - Fabian Rivera-Chávez (American Society for Microbiology, 2016)
ABSTRACT Salmonella enterica serovar Typhimurium can cross the epithelial barrier using either the invasion-associated type III secretion system (T3SS-1) or a T3SS-1-independent mechanism that remains poorly characterized. Here we show that flagellum-mediated motility supported a T3SS-1-independent pathway for entering ileal Peyer’s patches in the mouse model. Flagellum-dependent invasion of Peyer’s patches required energy taxis toward nitrate, which was mediated by the methyl-accepting chemotaxis protein (MCP) Tsr. Generation of nitrate in the intestinal lumen required inducible nitric oxide synthase (iNOS), which was synthesized constitutively in the mucosa of the terminal ileum but not in the jejunum, duodenum, or cecum. Tsr-mediated invasion of ileal Peyer’s patches was abrogated in mice deficient for Nos2, the gene encoding iNOS. We conclude that Tsr-mediated energy taxis enables S. Typhimurium to migrate toward the intestinal epithelium by sensing host-derived nitrate, thereby contributing to invasion of Peyer’s patches. IMPORTANCE Nontyphoidal Salmonella serovars, such as S. enterica serovar Typhimurium, are a common cause of gastroenteritis in immunocompetent individuals but can also cause bacteremia in immunocompromised individuals. While the invasion-associated type III secretion system (T3SS-1) is important for entry, S. Typhimurium strains lacking a functional T3SS-1 can still cross the intestinal epithelium and cause a disseminated lethal infection in mice. Here we observed that flagellum-mediated motility and chemotaxis contributed to a T3SS-1-independent pathway for invasion and systemic dissemination to the spleen. This pathway required the methyl-accepting chemotaxis protein (MCP) Tsr and energy taxis toward host-derived nitrate, which we found to be generated by inducible nitric oxide synthase (iNOS) in the ileal mucosa prior to infection. Collectively, our data suggest that S. Typhimurium enhances invasion by actively migrating toward the intestinal epithelium along a gradient of host-derived nitrate emanating from the mucosal surface of the ileum.